HUBUNGAN KETERAMPILAN BERPIKIR KREATIF DAN HASIL BELAJAR DENGAN RETENSI BIOLOGI MAHASISWA UPG 1945 NTT DALAM PEMBELAJARAN PREDICT OBSERVE EXPLAIN (POE) - Frengky Neolaka; Maya F. Roman; Eka C.G. Kerihi; Metri Manek; Susanti Mantolas (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The aim of this research is to analyze: the relationship between creative thinking skills and learning outcomes with student biology retention in POE learning. This type of research is descriptive correlational. The population in this study were all odd semester students of the 2023/2024 Academic Year, Biology Study Program, 1945 NTT Teachers' Association University. The sample used was class A students in semester 5. Data analysis using multiple linear regression showed that there was no relationship between creative thinking skills and learning outcomes and student retention through Predict Observe Explain learning. This is caused by students experiencing difficulty in extracting information stored in their memory, the time interval between carrying out the retention test and carrying out the posttest causes the information that students have to be eroded, there is interference so that the information is mixed with other information or shifted by other information.